IDEOLOGI PRANGGAPAN PAMFLET SOSIALISASI PELESTARIAN LINGKUNGAN DI KABUPATEN BURU - samsudiin sofie; Risman Iye; A. Yusdianti Tenriawali; Susiati Susiati (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2021)
ABSTARCT This research reveals the presumptive ideology of the socialization of environmental conservation pamphlets in Buru Regency. This research is a qualitative descriptive study. This means that in this study the researcher observed and analyzed the sentences in the Socialization Pamphlet for Environmental Conservation in Buru Regency through a pragmatic approach. The data source used for this study was the Environmental Conservation Socialization Pamphlet in Buru Regency, while the type of data in this study was written data, in the form of sentences in pamphlets containing presuppositions. This research reveals the types of presuppositions in the environmental preservation socialization pamphlet, namely: (1) existential presuppositions, (2) factive presuppositions, (3) lexical presuppositions, (4) structural presuppositions, and (5) counterfactual presuppositions while non-active presuppositions are not found. menemenyekuruh Government and LSM are trying to socialize environmental preservation in real terms in Buru Regency. This means that the pamphlet publisher does not use inactive presuppositions which in fact are presuppositions that are assumed to be incorrect or allow wrong understanding due to the use of uncertain or ambiguous words. Keywords: ideology; Presumption; Flyer; Buru Regency